2015
DOI: 10.1186/s12913-015-1166-8
|View full text |Cite
|
Sign up to set email alerts
|

The cost of dialysis in low and middle-income countries: a systematic review

Abstract: BackgroundThe cost of dialysis in low and middle-Income countries has not been systematically reviewed. The objective of this article is to systematically review peer-reviewed articles on the cost of dialysis across low and middle-income countries.MethodsPubMed and Embase databases were searched for the year 1998 to March 2013, and additional studies were added from Google Scholar search. An article was included if two reviewers agreed that it had reported cost of dialysis from low and middle-Income countries.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
104
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 31 publications
7
104
0
4
Order By: Relevance
“…Patients who were not on NHIF scheme had higher odds of poor outcomes. This finding is similar to other studies; a study conducted between 1998 and 2013 showed that haemodialysis in low and middle-income countries were faced with severe financial barriers to access dialysis services and dialysis patients could not afford dialysis on the free market [8, 18]. Studies from Nigeria and Sub Saharan Africa reported that many patients were unable to pay for the recommended adequate dialysis owing to high costs; only 6.8% of patients were able to afford haemodialysis beyond 3 months [1214].…”
Section: Discussionsupporting
confidence: 90%
“…Patients who were not on NHIF scheme had higher odds of poor outcomes. This finding is similar to other studies; a study conducted between 1998 and 2013 showed that haemodialysis in low and middle-income countries were faced with severe financial barriers to access dialysis services and dialysis patients could not afford dialysis on the free market [8, 18]. Studies from Nigeria and Sub Saharan Africa reported that many patients were unable to pay for the recommended adequate dialysis owing to high costs; only 6.8% of patients were able to afford haemodialysis beyond 3 months [1214].…”
Section: Discussionsupporting
confidence: 90%
“…En particular se requiere que la enfermera tenga habilidades interpersonales, competencias técnicas y clínicas para otorgar una atención segura y de calidad 5 . El personal de enfermería representa cerca del 45% de la fuerza de trabajo de una Unidad de Hemodiálisis (UHD), siendo parte de los costos directos de la diálisis 6,7 . Determinar la dotación de enfermeras para garantizar la seguridad del paciente sigue siendo una decisión importante que deben tomar los administradores de salud 8 .…”
unclassified
“…15 It is estimated at an average annual cost in Euros (€) of 50,000 per patient per year and €81,500 per patient per year, respectively, for peritoneal dialysis and HD in central Europe. 17,18 It is slowly starting to be subsidized by the state at varying proportions in many countries such as Cameroon, Kenya, Sudan, and others. 1 The consequences are huge and in addition to trauma related to lack of preparation for treatment initiation.…”
Section: Introductionmentioning
confidence: 99%
“…16 In SSA, CKD diagnosis usually occurs late in advanced stages requiring urgent RRT management. 18 In the Democratic Republic of the Congo (DRC), a low-income country with a gross domestic product per capita of US$271 and annual health expenditures of US $15 per capita, 19 CKD prevalence is 12.4% in Kinshasa, and 0.2% have ESRD. Complications installed during the disease's silent phase severely burden patients' future and treatment cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation